Perbandingan Efektivitas Video Animasi dan Busy Book Terhadap Pengetahuan Karies pada Anak Sekolah Dasar - Awaliah, Mutia; Laut, Deru Marah; Chaerudin, Denden Ridwan; Ningrum, Nining (Poltekkes Kemenkes Bandung, 2024)
Children in the 5th grade, aged 10-11, are particularly vulnerable to dental caries due to their limited understanding of the condition. Educating them becomes crucial, employing media such as animated videos and busy books, each with its advantages. This research aims to compare the effectiveness of animated videos versus busy books in enhancing knowledge about dental caries. This research is a quasi-experimental design with two group pretest and posttest. Sampling in this research was taken using the total sampling method from 5th grade students at SDN Kordon 03, as many as 46 people. The process includes pre-testing, educational interventions using the respective media is animated video or busy book, and post-testing. Results show both media significantly improve knowledge, with a Mann Whitney test indicating no statistical difference in effectiveness p value = 0,820 (0,820 > 0,05). This research shows that there is no rate gap between effectiveness animated video and effectiveness busy book towards knowledge of dental caries in 5th grade students at SDN Kordon 03, Bandung Regency.